Emotional approach coping and depressive symptoms in colorectal cancer patients: The role of the intimate relationship. Issue 5 (3rd September 2017) - Reese, Jennifer Barsky; Lepore, Stephen J.; Handorf, Elizabeth A.; Haythornthwaite, Jennifer A.
ABSTRACT: This study examined whether emotional approach coping was associated with lower depressive symptoms, and whether intimacy moderated this association, in 121 married/partnered colorectal cancer (CRC) outpatients. Prospective analyses of survey data on emotional approach coping, depressive symptoms, and intimacy measured at baseline and 6-month follow-up showed that depressive symptoms were inversely related to processing, expression, and intimacy. At baseline, the association between processing and depressive symptoms was moderated by intimacy: greater processing was associated with lower depressive symptoms only for those in relatively high-intimacy relationships. Enhancing emotional approach coping efforts and relationship quality may benefit CRC patients' adjustment.